American Values in John Lee Hancock’s The Blind Side - Haqiqi, Haqiqi; Harendika, Melania Shinta (Language Circle: Journal of Language and Literature, 2019)
The Blind Side is a movie derived from Michael Lewis’ The Blind Side: Evolution of a Game novel. This movie tells about Michael Oher, a poor black teenager, who is cared for by the country because his mother is a drug addict. The practices of American Values (Paul, 2014; Datesman, Kearny, Crandall, & Kearny, 2005; Doran & Litrell, 2013) can be found through the characters of Michael Oher, Burt Cotton, Leigh Anne Tuohy, and S.J. Tuohy. The data found in this movie is strengthened by Boggs and Petrie (2008)’s movie studies. The findings indicate that not every character in Hancock’s The Blind Side practices American values. Equality seems to be Americans’ ‚homework‛ evidenced by the Oher’s struggle to be accepted as a part of Wingate Christian School. Oher’s hard work, however, is fruitful when he is chosen as a quarterback which then brings material wealth to him. All in all, Hancock’s The Blind Side is a paradoxical example of American values practiced by the society.